Leveraging TikTok for Digital Daʿwah: Assessing Its Influence on Anti-Vaping Norms Among Malaysian University Students (Lembaga Contrarius Indonesia, 2026)
Amidst the escalating global health crisis of e-cigarette consumption, this study critically examines the intersection of religious digital outreach and health-seeking behavior s among university students. While conventional public health campaigns often struggle to resonate with tech-savvy demographics, this research investigates the potency of